Assessment of Antipsychotic Medications on Social Media: Machine Learning Study - Alvarez-Mon, Miguel A.; Donat-Vargas, Carolina; Santoma-Vilaclara, Javier; Anta, Laura de; Goena, Javier; Sanchez-Bayona, Rodrigo; Mora, Fernando; Ortega, Miguel A.; Lahera, Guillermo; Rodriguez-Jimenez, Roberto; Quintero, Javier; Álvarez-Mon, Melchor (Frontiers in Psychiatry, 2021)
Background: Antipsychotic medications are the first-line treatment for schizophrenia. However, non-adherence is frequent despite its negative impact on the course of the illness. In response, we aimed to investigate social media posts about antipsychotics to better understand the online environment in this regard. Methods: We collected tweets containing mentions of antipsychotic medications posted between January 1st 2019 and October 31st 2020. The content of each tweet and the characteristics of the users were analyzed as well as the number of retweets and likes generated. Results: Twitter users, especially those identified as patients, showed an interest in antipsychotic medications, mainly focusing on the topics of sexual dysfunction and sedation. Interestingly, paliperidone, despite being among one of the newest antipsychotics, accounted for a low number of tweets and did not generate much interest. Conversely, retweet and like ratios were higher in those tweets asking for or offering help, in those posted by institutions and in those mentioning cognitive complaints. Moreover, health professionals did not have a strong presence in tweet postings, nor did medical institutions. Finally, trivialization was frequently observed. Conclusion: This analysis of tweets about antipsychotic medications provides insights into experiences and opinions related to this treatment. Twitter user perspectives therefore constitute a valuable input that may help to improve clinicians' knowledge of antipsychotic medications and their communication with patients regarding this treatment.